Palliative care policy and practice in Kerala, India: Implications for Sustainable Development Goal 3—Health and well-being - S. Gowri; E. P. Abdul Azeez (Palliative Care and Social Practice)
The higher prevalence and incidents of chronic and life-threatening illnesses and the aging population living with morbidity and life-limiting conditions necessitate the need for care provisions like palliative care globally. Palliative care strives for the quality of life of patients with terminal illnesses and serious health conditions and their families. However, globally, access to palliative care remains very limited. The situation is similar in India, except for Kerala, where palliative care access to the needy population is almost universal. Kerala’s community palliative care model is globally acclaimed for its operation, which includes community participation and sustainability. The palliative care policy of Kerala, which was the first one in Asia, was a significant milestone in the palliative care movement of Kerala, as it mandated the interventions from government measures and further strengthened the community-managed palliative care interventions. The palliative care efforts in Kerala have significantly influenced the health scenario. However, discussion on the role of palliative care in achieving sustainable development goals (SDGs) is minimal. In this context, this article explores the policy and practices of palliative care in Kerala and its contribution to SDG-3, health and well-being. We have surrounded the discussion on the context of palliative care interventions and Sustainable Development Goal 3 through the unique features of the Kerala model of palliative care and its contribution to the healthcare scenario of the state. Through available literature and from the researchers’ first-hand experience, this article explores the reciprocity of palliative care interventions, policy, healthcare programs, and SDG-3. Documenting the potential of Kerala’s community-based palliative care for SDG-3 has implications for replications of this model in similar contexts.